Philippines apologizes for Taiwan logo gaffe during China's turnover of assault rifles - Dizon, Nikko (Philippine Daily Inquirer, 2017)
The Department of National Defense (DND) on Monday apologized to the Chinese government for the gaffe that DND spokesperson Arsenio Adolong described as "technical lapse."